Comparative transcriptome profiling of two Brassica napus cultivars under chromium toxicity and its alleviation by reduced glutathione. (December 2016) - Gill, Rafaqat; Ali, Basharat; Cui, Peng; Shen, Enhui; Farooq, Muhammad; Islam, Faisal; Ali, Shafaqat; Mao, Bizeng; Zhou, Weijun
Abstract Background Chromium (Cr) being multifarious industrial used element, is considered a potential environmental threat. Cr found to be a prospective water and soil pollutant, and thus it is a current area of concern. Oilseed rape (Brassica napus L.) is well known as a major source of edible oil around the globe. Due to its higher growth, larger biomass and capability to uptake toxic materialsB. napus is considered a potential candidate plant against unfavorable conditions. To date, no study has been done that described the Cr and GSH mechanism at RNA-Seq level. Results Both digital gene expression (DGE) and transcriptome profile analysis (TPA) approaches had opened new insights to uncover the several number of genes related to Cr stress and GSH alleviating mechanism in two leading cultivars (ZS 758 and Zheda 622) ofB. napus plants. Data showed that Cr inhibited KEGG pathways i.e. stilbenoid, diarlyheptanoid and gingerol biosynthesis; limonene and pentose degradation and glutathione metabolism in ZS 758; and ribosome and glucosinolate biosynthesis in Zheda-622. On the other hand, vitamin B6, tryptophan, sulfur, nitrogen and fructose and manose metabolisms were induced in ZS 758, and zeatin biosynthesis, linoleic acid metabolism, arginine and proline metabolism, and alanine, asparate and glutamate metabolism pathways in Zheda 622. Cr increased the TFs that were related to hydralase activity, antioxidant activity, catalytic activity phosphatase and pyrophosphatase activity in ZS 758, and vitamin binding and oxidoreductase activity in Zheda 622. Cr also up-regulated the promising proteins related to intracellular membrane bounded organelles, nitrile hyrdatase activity, cytoskeleton protein binding and stress response. It also uncovered, a novel Cr-responsive protein (CL2535.Contig1_All) that was statistically increased as compared to control and GSH treated plants. Exogenously applied GSH successfully not only recovered the changes in metabolic pathways but also induced cysteine and methionine metabolism in ZS 758 and ubiquinone and other terpenoid-quinone biosynthesis pathways in Zheda 622. Furthermore, GSH increased the level of TFs i.e. the gene expression of antioxidant and catalytic activities, iron ion binding and hydrolase activity as compared with Cr. Moreover, results pointed out a novel GSH responsive protein (CL827.Contig3_All) whose expression was found to be significantly increased when compared than Cr stress. Results further delineated that GSH induced TFs such as glutathione disulphide oxidoreducatse and aminoacyl-tRNA ligase activity, and beta glucosidase activity in ZS 758. Similarly in Zheda 622, GSH induced the TFs for instance DNA binding and protein dimerization activity. GSH also highlighted the proteins that were involved in transportation, photosynthesis process, RNA polymerase activity, and against the metal toxicity. These results indicated that cultivar ZS 758 had better metabolism and showed higher tolerance against Cr toxicity. Conclusion The responses of ZS 758 and Zheda 622 differed considerably at both physiological and transcriptional level. Moreover, RNA-Seq method explored the hazardous behavior of Cr as well as GSH up-regulating mechanism by activating plant metabolism, stress responsive genes, TFs and protein encyclopedia.